The Effects of a Stress Management Program on Knowledge and Perceived Self-efficacy among Participants from a Faith Community: A Pilot Study - Angeline Bushy; Marietta P. Stanton; Holly K. Freeman (Rural Nurse Organization; Binghamton University, 2004)
Educational programs can be an effective intervention for anticipatory guidance and health promotion across the lifespan. A particular concern for health care providers in rural areas is how to access high-risk populations and then provide programs that are culturally and linguistically appropriate. In recent years, religious congregations (faith communities) have been identified as an effective way to reach hidden and vulnerable populations in rural as well as urban settings. This article presents a pilot study describing an educational intervention related to stress management with participants who were accessed through a faith community. Both quantitative and qualitative tools were used the measure the dependent variables. Quantitative data were obtained with pencil and paper assessment tools measuring levels of self-efficacy and knowledge about stress. Qualitative data helped determine types of stress participants experienced and if stress management techniques learned in the course were used to manage day-to-day stressful situations. While the setting for this study was urban, the findings are highly relevant to nurses who provide care to rural and other underserved populations with limited access to health care.